Interactive and Indirect Effects of Anxiety and Negative Urgency on Alcohol-Related Problems - Menary, Kyle R. (Alcohol Clin Exp Res, 2015)
BACKGROUND: Although drinking for tension reduction has long been posited as a risk factor for alcohol-related problems, studies investigating anxiety in relation to risk for alcohol problems have returned inconsistent results, leading researchers to search for potential moderators. Negative urgency (the tendency to become behaviorally dysregulated when experiencing negative affect) is a potential moderator of theoretical interest because it may increase risk for alcohol problems among those high in negative affect. The present study tested a cross-sectional mediated moderation hypothesis whereby an interactive effect of anxiety and negative urgency on alcohol problems is mediated through coping-related drinking motives. METHOD: The study utilized baseline data from a hazardously drinking sample of young adults (N = 193) evaluated for participation in a randomized controlled trial of naltrexone and motivational interviewing for drinking reduction. RESULTS: The direct effect of anxiety on physiological dependence symptoms was moderated by negative urgency such that the positive association between anxiety and physiological dependence symptoms became stronger as negative urgency increased. Indirect effects of anxiety and negative urgency on alcohol problems (operating through coping motives) were also observed. CONCLUSIONS: Although results of the current cross-sectional study require replication using longitudinal data, the findings suggest that the simultaneous presence of anxiety and negative urgency may be an important indicator of risk for AUDs via both direct interactive effects and indirect additive effects operating through coping motives. These findings have potentially important implications for prevention/intervention efforts for individuals who become disinhibited in the context of negative emotional states.